Artificial Intelligence as a Catalyst for Sustainable MSME Development in the Halal and Green Economy - Rachmiatie, Atie; Sadikin, Aning Sofyan; Respitawulan; Lichandra, Funny (PT Inovasi Pratama Internasional, 2025)
Micro, small, and medium enterprises (MSMEs) serve as the backbone of Indonesia’s national economy, particularly in Bandung Regency, home to over 47,000 MSMEs. However, MSMEs face major challenges including limited marketing skills, low product quality due to insufficient digital access, limited awareness of halal certification, and environmentally unsustainable practices. This community service initiative addressed these issues by implementing an Asset-Based Community Development (ABCD) approach through workshops, technical assistance, and Penta helix collaboration involving academia, government, communities, and media. The program focused on enhancing digital literacy, introducing Artificial Intelligence (AI) for business efficiency, promoting Islamic finance, and fostering a halal and green economic ecosystem. The results show a significant increase in business actors’ interest and awareness in adopting AI and digital tools, especially in creating AI-generated social media content for marketing. Moreover, participants demonstrated improved understanding and capacity to pursue halal certification and eco-friendly packaging. The key outcome of the program is the establishment of a cross-sectoral coordination forum and the organization of an MSME exhibition as a sustainable effort to strengthen MSEs competitiveness.